SYSTEM ANALYSIS OF THE FOUR-PRONG LEGGED ACCELEROMETER BASED ON TRAPEZOIDAL VARIABLE CROSS-SECTION BEAM - LU KunLei; SUN JiangHong; YI YuanLin; DU HongChen (Jixie qiangdu)
Combining the four-prong legged acceleration system dynamic response,stability and sensitivity of support stiffness,a trapezoidal beam with variable cross section was designed and optimized. The dynamic model of the accelerometer was established and a relationship was found between the system dynamic response parameters and the beam rigidity. The trapezoidal variable cross-section beam rigidity-size relation was deduced with a bending mathematical model. The size requirements were raised by strength. By analyzing the system stability and sensitivity of the accelerometer,the beam rigidity was obtained.Compared with uniform cross-section under the equal rigidity in the no-detection direction,the trapezoidal variable section beam reduces the stiffness in detection direction with the equal stress on the critical section,improves the system sensitivity and dynamic output characteristics. However,quality greatly reduces.